Som en blixt från klar himmel - Zackariasson, Maria (Tidsskrift for kulturforskning, 2007)
Every day a number of dramatic events take place in the world. Some of them make a bigger impression than others, because of their size, exceptionality or closeness to us. In this article I look at three such extraordinary events; when the Titanic sank in 1912, when the ferry Estonia went under in 1994 and the Tsunami in South-East Asia in 2004. All of these disasters had special significance for people in the Scandinavian countries, since they affected a number of Scandinavian citizens, even though they took place outside of the national borders. They were also enormous media events, and in this article I particularly look at how the emotions connected with the disasters were portrayed in the newspaper coverage, with examples from the evening press in Sweden and Norway. Central issues include: What are the differences between 1912 and 2004 when it comes to how emotions are displayed in the news media? How are the survivors and the relatives of the victims treated in the press? I discuss this in relation to the concept of emotional norms.